2020
DOI: 10.3390/horticulturae6040109
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Growth and Morphology of Vegetable Seedlings with Supplemental Far-Red Enriched LED Lights in a Plant Factory

Abstract: Although light-emitting diode (LED) lamps have been broadly applied in horticultural production to improve plant yield and quality, compared to natural light there is a disadvantage in the lack of far-red light in the LED spectrum. Far-red light has been studied widely to control plant growth and development. Therefore, this study aimed to find the effect of supplemental far-red-enriched LED lights to control the growth of tomato, red pepper, cucumber, gourd, watermelon and bottle gourd seedlings. The treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The morphometric parameters of plants depend on the growing conditions and the action of exogenous factors and are important in assessing their physiological state [ 25 , 26 ]. Potato plants of the cv.…”
Section: Discussionmentioning
confidence: 99%
“…The morphometric parameters of plants depend on the growing conditions and the action of exogenous factors and are important in assessing their physiological state [ 25 , 26 ]. Potato plants of the cv.…”
Section: Discussionmentioning
confidence: 99%
“…According to a previously reported study, when lettuce was treated by adding FR light to blue and red light, the biomass increased by 39% and 25%, respectively, and the appearance of the plant was changed to improve the light use efficiency [ 25 ]. In addition, Hwang et al [ 26 ] reported that as a result of cultivating tomatoes, peppers, cucumbers, and watermelons by supplementing far-red rays with cool-white LEDs, the hypocotyl length and dry weight of seedlings increased as the light intensity of far-red rays increased. Furthermore, Tan et al [ 27 ] reported far-red-induced changes in plant height, leaf structure and shape, stomatal response, chloroplast development, biomass, photosynthetic pigment and fluorescence, electron transport, carbon assimilation, etc., in various crops.…”
Section: Introductionmentioning
confidence: 99%
“…Others have shown that FR radiation causes an increase in stem elongation in plants such as tomato (Hwang et al, 2020;Zhang et al, 2019), lettuce (Lactuca sativa) (Lee et al, 2015), and various ornamental species (Park and Runkle, 2019). It is widely accepted that a shade avoidance response mediated by a low phytochrome photostationary state produced under a low red:FR ratio is responsible for this response (Kalaitzoglou et al, 2019;Zhen et al, 2022), which corresponds with our results for ii For each cultivar, means within columns followed by the same letter are not different based on Tukey's honestly significant difference test at P # 0.05 (n = 8 for main effects; n = 4 for interactions).…”
Section: Resultsmentioning
confidence: 99%